Microbiological and Physicochemical Properties of Grapes (Vitis vinifera) Treated with Chitosan Incorporated with Citronella Oil - Syarah Syahindah Abdullah,; Munira Zainal Abidin, (Enhanced Knowledge in Sciences and Technology, 2024)
Chitosan is one of the most researched antimicrobial agents due to its ability for food packaging to form films and coatings. It also exhibits antimicrobial activity against a variety of fungus, yeasts, and bacteria that are found in food, with greater efficacy against yeast that causes fungal development in grapes (Vitis vinifera) during post-harvest storage. The purpose of this study is to assess the microbiological and physicochemical properties of grapes coated with chitosan incorporated with citronella oil by spraying technique. The treated grapes were stored at 4°C for 15 days. The highest concentration of citronella essential oil with 1.5% (T4) showed to be the most successful as a coating since it has the lowest pH value (3.56 to 3.61), excellent visual qualities, and higher skin strength (83.57 ± 2.72 to 109.28 ± 7.55), enhanced elasticity (18.19 ± 3.45 to 24.13 ± 0.43), and preserved moisture content (80.07 ± 0.70 to 82.57 ± 2.13). Mold and yeast counts were lowest (3.36 Log CFU/g) in the T4 coating treatment. The findings indicated that adding essential oil to chitosan can extend its shelf life.